Uhakiki wa fasihi :misingi na vipengele vyake - WAMITILA, K. W. (Nairobi : Phoenix Publishers, 2002)
The fundamental aspects of literary criticism.
Includes bibliographical references (p. 212-223) and index.
In Swahili.
Keywords: Swahili language -- Texts